Larvicidal activity of Xenorhabdus and Photorhabdus bacteria against Aedes aegypti and Aedes albopictus - Apichat Vitta; Punnawat Thimpoo; Wipanee Meesil; Thatcha Yimthin; Chamaiporn Fukruksa; Raxsina Polseela; Bandid Mangkit; Sarunporn Tandhavanant; Aunchalee Thanwisai (Asian Pacific Journal of Tropical Biomedicine, 2018)
Objective: To evaluate the efficacy of symbiotic bacteria, Xenorhabdus indica, Xenorhabdus stockiae, Photorhabdus luminescens subsp. akhurstii and Photorhabdus luminescens subsp. hainanensis as a larvicide against Aedes aegypti and Aedes albopictus. Methods: Larvae (L3-L4) of Aedes aegypti and Aedes albopictus were given 2 mL of a suspension 107-108 CFU/mL of each symbiotic bacterium. Distilled water and Escherichia coli ATCC® 25922 were used as the control. The mortality rate of the larval mosquitoes was observed at 24, 48, 72 and 96 h. The experiment was performed in triplicates. Results: The larvae of both Aedes species started to die at 24 h exposure. Aedes aegypti showed the highest mortality rate (87%-99%), 96 h after exposure to Xenorhabdus stockiae (bNBP22.2_TH). The mortality rate of Aedes albopictus was between 82% and 96% at 96 h after exposure to Xenorhabdus indica (bKK26.2_TH). Low effectiveness of distilled water and Escherichia coli ATCC® 25922 were observed in both Aedes larvae, with a mortality rate of 2% to 12%. Conclusions: The study confirms the oral toxicity of Xenorhabdus and Photorhabdus bacteria against Aedes spp. Xenorhabdus stockiae and Xenorhabdus indica may be an alternative agent for control Aedes spp. This is basic information for further study on the mechanism of action on Aedes larvae or application to control mosquito larvae in the community.